Pre-weaning growth of Boer x Peranakan Etawah goats - T Kostaman; I-K Sutama (Jurnal Ilmu Ternak dan Veteriner, 2005)
An experiment was conducted to study the growth patterns of Boer x Peranakan Etawah (PE) crossbred during pre-weaning period, at the Indonesian Research Institute for Animal Production, Ciawi-Bogor. Sixty-one kids were used in this experiment. They were reared with their mothers in group pen (3 x 4 m), with each pen contained 6-7 does. Does were fed of 2.5 kg freshlychopped King Grass and 0.7 kg concentrate head-1 day-1. Research results showed that birth weight of Boer x PE kids (group A) were significantly higher than those of PE kids (group B) (4.29 ± 0.63 vs 3.71 ± 0.89 kg/head, P<0.05). However, average preweaning daily weight gain (ADG) (116.40 ± 49.95 vs 105.29 ± 28.36 g/head, P>0.05) and weaning weight (14.64 ± 4.56 vs 13.30 ± 2.71 kg/head, P>0.05) were not significantly different between the groups. Pre-weaning mortality of the kids was relatively high in both group A (25%) and B (21,21%). While sex ratio (male : female) was 57.14 : 42.86% in group A and 51,52 : 48,48% in group B.     Key Words: Growth, PE, Boer Goat, Pre-Weaning